PENGARUH CAR, FDR, DAN BOPO DENGAN NPF SEBAGAI VARIABEL MODERATING TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH DI INDONESIA (Studi Empiris pada Bank Umum Syariah di Indonesia Periode 2014 Q1 – 2018 Q4) - Taufik Kurnia; Sugeng Wahyudi (Faculty of Economics and Business | Universitas Diponegoro, 2021)
The purpose of this study was to determine the effect of CAR, FDR, and BOPO with NPF as a moderating variable on the Profitability of Islamic Commercial Banks in Indonesia in the period 2014 to 2018. Profitability is proxied by ROA as a measure of the amount of profit generated.The sample in this study is Islamic commercial bank in Indonesia during the period 2014-2018. The number of samples were 11 banks taken by purposive sampling method. The analytical method of this study uses MRA (Moderated Regression Analysis) with the SPSS 25 program which previously passed the classic assumption test.The results of this study indicate that CAR has a positive and significant effect on ROA. FDR has a positive no significant effect on ROA. BOPO has a negative and significant effect on ROA. NPF able to moderate CAR relationship effect on ROA. NPF not being able to moderate FDR relationship effect on ROA. NPF able to moderate BOPO relationship effect on ROA.